PWM CONTROLLED FOUR SWITCH THREE PHASE INVERTER FED INDUCTION MOTOR DRIVE - Maharudra S. Shinde; Sanjay M Shinde (International Journal of Innovations in Engineering Research and Technology, 2021)
In this paper four switch three phase inverter (FSTPI) fed induction motor drive is studied and analysed using simulations based on MATLAB SIMULINK. The input voltage to the induction motor is in pulse width modulated form. A simple sine-pulse-width-modulation-based (SPWM) control strategy has been used. It is observed that the induction motor stator current is sinusoidal in nature. It is found that motor speed is attaining steady state speed satisfactorily. The FSTPI fed induction motor drive is found quite acceptable considering its performance, cost reduction due to reduced switch countthe switching losses, the complexity of the control algorithms and the interface circuits to generate six PWM logic signals. Both PWM and SPWM techniques are implemented for switching. The performance of the motor and the Total Harmonic Distortion (THD) are compared in both of these techniques. Finally a comparison between the performance of induction motor fed from three phase six-switch based inverter and three phase four-switch based inverter is carried out.